Post-biopsy to Surgery Interval Tends to Increase Axillary Nodal Metastasis, Especially in Early Breast Cancer Patients - Phatcharawan Prasitviset; Pongthep Pisarnturakit; Adune Ratanawichitrasin (Siriraj Medical Journal)
Objective: Delays between diagnosis and breast cancer surgery may raise concerns about tumor progression. Tumors of the same size should exhibit same proportions of N staging. We aimed to evaluate the impact of time to surgery (TTS) on the proportion of metastatic axillary lymph nodes (N-Staging), controlled by tumor size.